Case Report: Lacosamide unmasking SCN5A-associated Brugada syndrome in a young female with epilepsy - Shen, Ying-Chi; Wu, Jen-Chueh; Lin, Ting-Tse; Chang, Kai-Chung; Su, Jen-Jen; Juang, Jyh-Ming Jimmy (Frontiers in Cardiovascular Medicine, 2024)
Background Lacosamide is frequently used as a mono- or adjunctive therapy for the treatment of adults with epilepsy. Although lacosamide is known to act on both neuronal and cardiac sodium channels, potentially leading to cardiac arrhythmias, including Brugada syndrome (BrS), its adverse effects in individuals with genetic susceptibility are less understood. Case We report a 33-year-old female with underlying epilepsy who presented to the emergency department with a four-day history of seizure clusters, and was initially treated with lacosamide therapy. During the intravenous lacosamide infusion, the patient developed sudden cardiac arrest caused by ventricular arrhythmias necessitating resuscitation. Of note, the patient had a family history of sudden cardiac death. Workup including routine laboratory results, 12-lead electrocardiogram (ECG), echocardiogram, and coronary angiogram was non-specific. However, a characteristic type 1 Brugada ECG pattern was identified by ajmaline provocation testing; thus, confirming the diagnosis of BrS. Subsequently, the genotypic diagnosis was confirmed by Sanger sequencing, which revealed a heterozygous mutation (c.2893C>T, p.Arg965Cys) in the SCN5A gene. Eventually, the patient underwent implantable cardioverter-defibrillator implantation and was discharged with full neurological recovery. Conclusion This case highlights a rare but lethal adverse event associated with lacosamide treatment in patients with genetic susceptibility. Further research is warranted to investigate the interactions between lacosamide and SCN5A variants.